High predictive efficacy of integrase strand transfer inhibitors in perinatally HIV-1-infected African children in therapeutic failure of first- and second-line antiretroviral drug regimens recommended by the WHO. (19th March 2019) - Mboumba Bouassa, Ralph-Sydney; Mossoro-Kpinde, Christian Diamant; Gody, Jean-Chrysostome; Veyer, David; Péré, Hélène; Matta, Mathieu; Robin, Leman; Grésenguet, Gérard; Charpentier, Charlotte; Bélec, Laurent
Abstract: Objectives: The predictive efficacy of integrase (IN) strand transfer inhibitors (INSTIs) was investigated in HIV-infected children born to HIV-infected mothers in Africa. Methods: Plasma was collected at the Complexe Pédiatrique of Bangui, Central African Republic, from INSTI-naive children ( n = 8) and adolescents ( n = 10) in virological failure (viral load >1000 copies/mL) after 5 years of first- and/or second-line combination ART (cART). IN, reverse transcriptase (RT) and protease (P) genes were genotyped and drug resistance mutations (DRMs) to INSTIs, NRTIs, NNRTIs and PIs were interpreted using the Stanford algorithm. Results: Successful IN, RT and P genotypes were obtained for 18, 13 and 15 children (median age 11 years, range 5–18; 8 were female), respectively. Two (2/18; 11.1%) viruses from children treated with a first-line regimen had INSTI DRMs at codon 138 (E138K and E138T), which is known to harbour major resistance mutations, and also had the accessory mutations L74I, G140K, G140R and G163R. The majority (16/18; 88.9%) of HIV-1 IN sequences demonstrated full susceptibility to all major INSTIs with a high frequency of natural polymorphic mutations. Most (12/15; 80%) genotyped viruses harboured at least one major DRM conferring resistance to at least one of the WHO-recommended antiretroviral drugs (NNRTIs, NRTIs and PIs) prescribed in first- and second-line regimens. Conclusions: INSTIs could be proposed in first-line regimens in the majority of African children or adolescents and may constitute relevant therapeutic alternatives as second- and third-line cART regimens in HIV-infected children and adolescents living in sub-Saharan Africa.